Analysis of Resilience Among Married Students at the Faculty of Da'wah and Communication, State Islamic University of North Sumatra - Syahfitri, Selly; Metia, Cut (Madania: Jurnal Ilmu-Ilmu Keislaman, 2024)
This study aims to analyze the resilience of married students at the Faculty of Da'wah and Communication, UIN Sumatera Utara, and the factors contributing to its formation. The main issue addressed is how married students manage dual roles as students and spouses, as well as the challenges they face in balancing academic responsibilities and family obligations. This research employs a qualitative descriptive method using in-depth interviews, observation, and documentation study techniques. The sample consists of four married students actively attending lectures. The results indicate that the resilience of married students is influenced by their adaptability, the importance of rest for mental health, self-confidence, and support from their spouses and families. The study implies that educational institutions need to provide mentoring programs and counseling services to assist married students in overcoming academic and personal life challenges.